Detection of limited-energy α particles using CR-39 in laser-induced p −11B reaction - Wang, Putong; Deng, Xiangai; Ma, Zhiguo; Fu, Changbo; Fan, Lulin; Wang, Qingsong; Xu, Jiancai; Xu, Tongjun; Ji, Liangliang; Shen, Baifei; Liu, Yancheng; Cao, Xiguang; et al. (Frontiers in Physics, 2023)
Due to the harsh radiation environment produced by strong laser plasma, most of the detectors based on semiconductor can not perform in good condition. It is then important to develop new detecting techniques with higher detection threshold and high charged particles resolution for investigating nuclear fusion reactions in laser-plasma environments. CR-39 (Columbia Resin No. 39) detector is sensitive mainly to ions while insensitive to the backgrounds such as electrons and photons. The detector has been widely used to detecting charged particles in laser-plasma environments. In this work, we use a Potassium-Ethanol-Water (PEW) etching solution to reduce the proton sensitive of CR-39 by raising the detection threshold for the research of laser-induced 11 B(p, α)2α reaction. We calibrated the 3-5 MeV α particles in etching condition of 60 o C PEW-25 solution[17%KOH + 25%C2 H5 OH + 58%H2O ] and compared them with the manufacturer’s recommended etching conditions of 6.25N NaOH aqueous solution at 98 degree in our laser-induced nuclear reactions experiment. The results indicate, with the PEW-25 solution, CR-39 is more suitable to discriminate α tracks from the proton background in our experiment. We also present a method to estimate the minimum detection range of α energy on specific etching condition in our experiment.